Impacts of Climate Change on Marine Fisheries and Aquaculture in Chile - Eleuterio Yáñez; Nelson A. Lagos; Ricardo Norambuena (John Wiley &Sons Ltd., 2025)
Chile, according to the criteria of the United Nations Framework Convention on Climate Change (UNFCCC), is highly vulnerable to climate change since it has coastline areas of low height, arid, semi-arid and forest areas, susceptibility to natural disasters, areas prone to droughts and desertification, urban areas with atmospheric pollution issues and mountain ecosystems. Ocean acidification, variations in the sea temperature and level, as well as the increase in the frequency and intensity of extreme events, such as surges, rainfall, El Niño-Southern Oscillation (ENSO), have a direct impact on the ocean’s primary and secondary production, on the biological cycles and their seasonality, on the distribution of fishing resources, and on the supporting infrastructure for fisheries and aquaculture activities, which ultimately affect the benefits of the communities dedicated to the extraction of fishing resources and small-scale aquaculture activities. The assessment of these potential scenarios will demand further 10 Impacts of Climate Change on Marine Fisheries and Aquaculture in Chile Eleuterio Yáñez1, Nelson A. Lagos2,13, Ricardo Norambuena3, Claudio Silva1, Jaime Letelier4, Karl-Peter Muck5, Gustavo San Martin6, Samanta Benítez2,13, Bernardo R. Broitman7,13, Heraldo Contreras8, Cristian Duarte9,13, Stefan Gelcich10,13, Fabio A. Labra2, Marco A. Lardies11,13, Patricio H. Manríquez7, Pedro A. Quijón12, Laura Ramajo2,11, Exequiel González1, Renato Molina14, Allan Gómez1, Luis Soto15, Aldo Montecino16, María Ángela Barbieri17, Francisco Plaza18, Felipe Sánchez18, Antonio Aranis18, Claudio Bernal18 and Gabriela Böhm18 1 Escuela de Ciencias del Mar, Pontificia Universidad Católica de Valparaíso, Chile 2 Centro de Investigación e Innovación para el Cambio Climático, Facultad de Ciencias, Universidad Santo Tomás, Santiago, Chile 3 COPAS Sur Austral, Universidad de Concepción, Chile 4 Departamento de Oceanografia y Medioambiente, Instituto de Fomento Pesquero, Blanco, Valparaiso, Chile 5 Advisor (GIZ, German Agency for International Cooperation) in climate change adaptation at the Ministry of Environment, Santiago, Chile 6 Punto Focal de Cambio Climático, Subsecretaría de Pesca y Acuicultura, Valparaíso, Chile 7 Centro de Estudios Avanzados en Zonas Áridas (CEAZA), Facultad de Ciencias del Mar, Universidad Católica del Norte, Coquimbo, Chile 8 Instituto de Fomento Pesquero, Centro Tecnológico para la Acuicultura Putemún, Castro, Chile 9 Departamento de Ecología y Biodiversidad, Facultad de Ecología y Recursos Naturales, Universidad Andres Bello, Santiago, Chile 10 Center of Applied Ecology and Sustainability, Pontificia Universidad Católica de Chile, Santiago, Chile 11 Departamento de Ciencias, Facultad de Artes Liberales & Facultad de Ingeniería y Ciencias, Universidad Adolfo Ibáñez, Santiago, Chile 12 Department of Biology, University of Prince Edward Island, Charlottetown, Canada 13 Center for Multiple-Drivers on Marine Socio-Ecological Systems (MUSELS), Universidad de Concepcion, Chile 14 Department of Economics, University of California Santa Barbara, USA 15 Departamento de Física, Facultad de Ciencias, Universidad del Bío, Concepción, Chile 16 Departamento de Geofísica e Instituto Milenio de Oceanografía, Universidad de Concepción, Chile 17 Subsecretaría de Pesca y Acuicultura, Valparaíso, Chile 18 Instituto de Fomento Pesquero, Valparaíso, Chile 10.1002/9781119154051.ch10, Downloaded from https://onlinelibrary.wiley.com/doi/10.1002/9781119154051.ch10 by Cochrane Malaysia, Wiley Online Library on [14/12/2022]. See the Terms and Conditions (https://onlinelibrary.wiley.com/terms-and-conditions) on Wiley Online Library for rules of use; OA articles are governed by the applicable Creative Commons License 240 Climate Change Impacts on Fisheries and Aquaculture: A Global Analysis information and knowledge regarding the ocean–atmosphere system at regional and local levels, as well as the development and application of models that allow scenarios to be established with high confidence of occurrence in the future (Fuenzalida et al., 2007; Yáñez et al., 2014). At the same time, in order to adapt to future weather and ocean scenarios throughout Chile, knowledge and management actions for fisheries and aquaculture should be communicated.